The Role And Importance Of The Management System In Improving The Quality Of Education - Ibragimova Gulnoza Sayidmurodovna (Global Scientific Publishing, 2024)
This article discusses the interaction of improving the management system in general secondary schools and improving the quality of education
Keywords: Personnel; academic institution; educational technology